Plant growth-promoting bacterial endophytes from sugarcane and their potential in promoting growth of the host under field conditions - Chauhan, H.; Bagyaraj, D. J.; Sharma, A.
Ten endophytic bacteria were isolated from different sugarcane varieties growing in the Crop Research Centre, Pantnagar on nitrogen-free medium. Plant growth-promoting potential of the isolates was reported in terms of indole acetic acid (IAA)production, phosphorus solubilization, siderophore production and antagonistic action against the pathogen Colletotrichum falcatum, which causes red rot disease in sugarcane in vitro. All the isolates were able to produce IAA (4.8-9 ?g ml?1); three isolates (H3, H5 and H14)solubilized insoluble phosphorus on Pikovaskaya's agar; two isolates (H10 and H14)showed siderophore production on Chrome-azurol S (CAS)agar and antagonism against C. falcatum was exhibited by two isolates (H14 and H15)in a dual plate assay. 16 S rRNA sequencing identified isolates H3 and H12 as Pseudomonas spp., and H8, H14 and H15 as Bacillus spp. A field experiment on sugarcane was conducted with five plant growth-promoting bacterial endophytes Pseudomonas spp. (H3 and H12)and Bacillus spp. (H8, H14 and H15)along with standard strains of Gluconacetobacter and Azospirillum spp. Plant height, chlorophyll content, total nitrogen and cane length were significantly higher in almost all inoculated plants compared with the uninoculated control. An increase of 40 percent in cane yield over the control was obtained after inoculation with isolate H15 (Bacillus spp.). This was statistically on par with the standard endophyte Gluconacetobacter diazotrophicus, which resulted in 42 percent increased cane yield. Identification of new diazotrophs and their promising results towards improving plant growth in the field suggest their use as inoculants in future.